As missões do e no Rio Grande do Sul: os nomes próprios e as designações no processo de narratividade - Klein, Mirela Schröpfer (2024)
This thesis, developed from the theoretical and methodological foundations of materialist Discourse Analysis and connected to the Graduate Program in Language Studies, with an emphasis on Linguistic Studies, at the Federal University of Santa Maria (PPGL/UFSM), aimed to understand the meaning effects resonating in history and its narrativity through the observation of the functioning of proper names and/or their erasure. The research focused on bibliographic books from the 1900s that address events in Caaró — located in the municipality of Caibaté/RS — and in Assunção do Ijuí — located in the municipality of Pirapó/RS — in the year 1628, as well as two beatification processes: the beatification process of Fathers Roque González, Afonso Rodrigues, and João de Castilho, and the progression of the beatification process of Sepé Tiarajú. We conducted a study on these documents to understand how the names that appear in history function discursively and resonate in narrativity. For this, we analyzed discursive excerpts, starting from the observation of the occurrence and effect of repeatability of the name Nheçu, an important indigenous leader, and/or the designations attached to the specific proper name. Additionally, in the beatification process of Fathers Roque González, Afonso Rodrigues, and João de Castilhos, discursive excerpts related to the construction of narrativity from religious discourse were mobilized, highlighting the importance of writing for this constitution. In the excerpts taken from the document regarding the progression of the beatification process of Sepé Tiarajú, the factor of repeatability, as well as the proper names appearing in such documentation, were again considered. With this in mind, analytical gestures were made which considered the aforementioned theoretical framework for their constitution, thus mobilizing concepts that were essential to our understanding. In these gestures, we understood that proper names signify in history based on different processes, and in the specific socio-historical context of this research, these names resonate in the constitution of meaning effects, solidifying meanings and narratives related to those names. Moreover, we concluded that these proper names, linked to history, can signify in different ways in the social process of subjectivation.